Asymmetric synthesis of the tetracyclic core of bufogargarizin C by an intramolecular [5 + 2] cycloaddition. Issue 1 (12th November 2018) - Fan, Jian-Hong; Hu, Ya-Jian; Guo, Qiang; Li, Shaoping; Zhao, Jing; Li, Chuang-Chuang
Abstract : A concise asymmetric synthesis of the synthetically challenging 7/5/6/5-tetracyclic core of bufogargarizin C by a unique intramolecular [5 + 2] cycloaddition was reported. Abstract : A concise asymmetric synthesis of the core of bufogargarizin C, which contains a synthetically challenging 7/5/6/5-tetracyclic ring system, is reported. This approach features a unique Brønsted acid-mediated intramolecular [5 + 2] cycloaddition, which is the first example of intramolecular [5 + 2] cycloaddition of an allene moiety mediated by acid.